2016
DOI: 10.1371/journal.pone.0150860
|View full text |Cite
|
Sign up to set email alerts
|

Soil Quality Indexing Strategies for Evaluating Sugarcane Expansion in Brazil

Abstract: Increasing demand for biofuel has intensified land-use change (LUC) for sugarcane (Saccharum officinarum) expansion in Brazil. Assessments of soil quality (SQ) response to this LUC are essential for quantifying and monitoring sustainability of sugarcane production over time. Since there is not a universal methodology for assessing SQ, we conducted a field-study at three sites within the largest sugarcane-producing region of Brazil to develop a SQ index (SQI). The most common LUC scenario (i.e., native vegetati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
0
21

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(117 citation statements)
references
References 63 publications
5
91
0
21
Order By: Relevance
“…These effects would affect the CEC provided by functional groups of SOM and reduce enzymes activity (Table S1). Such results are consistent with the strong influence of SOM on biological processes occurring in the soil and ultimately would boost plant growth (Cherubin et al, ; Lal, ). Thus, the recovery of SOM during the early stages of land reclamation in mined areas also should impact positively on other soil quality indicators (e.g., LOC, BD, and AcP), which are critical to achieve self‐sustaining systems (Chaudhuri, McDonald, Skousen, & Pena‐Yewtukhiw, ; Hu, Niu, Zeng, & Wang, ).…”
Section: Discussionsupporting
confidence: 86%
“…These effects would affect the CEC provided by functional groups of SOM and reduce enzymes activity (Table S1). Such results are consistent with the strong influence of SOM on biological processes occurring in the soil and ultimately would boost plant growth (Cherubin et al, ; Lal, ). Thus, the recovery of SOM during the early stages of land reclamation in mined areas also should impact positively on other soil quality indicators (e.g., LOC, BD, and AcP), which are critical to achieve self‐sustaining systems (Chaudhuri, McDonald, Skousen, & Pena‐Yewtukhiw, ; Hu, Niu, Zeng, & Wang, ).…”
Section: Discussionsupporting
confidence: 86%
“…The rates of C emissions from cutting and burning of tropical forest in the Amazon obtained in this study (Figure 2) are similar to those of 58 to 102 Mg ha −1 reported by Kauffman et al [43] and 100 to 200 Mg ha −1 by Dias-Filho et al [44]. In addition, conversion of native vegetation to agroecosystems adversely affects numerous other ecosystem services such as sustaining agronomic production, maintaining freshwater supply and soil quality, regulating climate and air quality, ameliorating infectious diseases and preserving biodiversity [45][46][47][48].…”
Section: Ghg Emissionssupporting
confidence: 87%
“…The growing interest in biofuels has resulted in a new demand for arable land for bioenergy crop production. Land use change (LUC) is one of the greatest threats to soil quality (Bonilla‐Bedoya, López‐Ulloa, Vanwalleghem, & Herrera‐Machuca, ; Cherubin, Karlen, Cerri, et al., ), as it can have significant impacts on soil biodiversity (Franco et al., ), carbon storage (Mello et al., ) and ecosystem services (Foley et al., ). Brazil is the world’s largest sugarcane producer with 8.59 million ha of cultivation area and production of 29 Mt of sugar and 33 billion L of ethanol (CONAB, ).…”
Section: Introductionmentioning
confidence: 99%